Disability and Depression among Population Aged 18-59 Years in Central Sulawesi Province: Analysis of Riskesdas 2018 - Ajeng Tias Endarti; Nydia Andriani; Eko Setyo Pambudi (Faculty of Public Health, Hasanuddin University, Makassar, 2020)
The prevalence of depression among the general population in CentralSulawesi was the highest in Indonesia (12.3%). Scholars revealed thatdisability was one of the main contributing factors of depression and in Central Sulawesi almost half of population was reported having disability (42.1%). This study was intended to identify the association of disability and depression in Central Sulawesi. Cross sectional design study was conducted with utilization of secondary data collection from Riskesdas 2018. Depression, as the main outcome, was assessed by the Mini International Neuropsychiatric Interview (MINI), meanwhile, disability was assessed by the WHODAS instrument. The relationship between these two variables was adjusted by several confounders, namely age, gender, marital status, educational status, and employment status. A 11,9% of 11,926 respondent aged 18-59 years old, was depressed and almost half of them reporting disability (42.1%) and among those who were disabled, one-fifth weredepressed. The risk of depression among respondents with disabilities was 3.25 times higher (p=0.000; 95% CI 2.9-3.6) compared to respondentswithout disability after controlled by confounders (gender, marital status,educational status, and employment status). It is recommended that routine mental health screening needs to be done at Posyandu, Posbindu and among patients at Primary Health Care. Besides, health promotion focused on physical activity in a community such as community gymnastics during theweekend.